Neurobehavioral Deficits After Subarachnoid Hemorrhage in Mice: Sensitivity Analysis and Development of a New Composite Score - Matsumura, Kanako (J Am Heart Assoc, 2019)
BACKGROUND: Because of the failure of numerous clinical trials, various recommendations have been made to improve the usefulness of preclinical studies. Specifically, the STAIR (Stroke Therapy Academic Industry Roundtable) recommendations highlighted functional outcome as a critical measure. Recent reviews of experimental subarachnoid hemorrhage (SAH) studies have brought to light the numerous neurobehavioral scoring systems that are used in preclinical SAH studies. To gain insight into the utility of these scoring systems, as well as to identify a scoring system that best captures the deficits caused by SAH in mice, we designed the current study. METHODS AND RESULTS: Adult male C57BL/6J mice were used. One cohort of mice was randomly allocated to either sham or SAH and had functional testing performed on days 1 to 3 post‐SAH using the modified Bederson Score, Katz Score, Garcia Neuroscore, and Parra Neuroscore, as well as 21 individual subtests. A new composite neuroscore was developed using the 8 most diagnostically accurate subtests. To validate the use of the developed composite neuroscore, another cohort of mice was randomly assigned to either the sham or SAH group and neurobehavior was evaluated on days 1 to 3, 5, and 7 after injury. Receiver operating characteristic curves were used to analyze the diagnostic accuracy of each scoring system, as well as the subtests. Of the 4 published scoring systems, the Parra Neuroscore was diagnostically accurate for SAH injury in mice versus the modified Bederson and Katz Scores, but not the Garcia Neuroscore. However, the newly developed composite neuroscore was found to be statistically more diagnostically accurate than even the Parra Neuroscore. CONCLUSIONS: The findings of this study promote use of the newly developed composite neuroscore for experimental SAH studies in mice.